Prognostic significance of CEBPA gene mutations in patients with acute myeloid leukemia - Pieronkiewicz, Marzena; Lewandowski, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2010)
Transcription factors play important role in the process of cells differentiation and intracellular signalling. The gene encoding CEBPA transcription factor is one of the master regulators of granulopoiesis. Mutations of CEBPA are presumed to be involved in emergence and progression of acute myeloid leukemia (AML) and are associated with good prognosis in AML patients. This article pinpoints the role of CEBPA in granulocyte differentiation regulation, types of CEBPA mutations and recommended methods of their identification. Independently, prognostic value of CEBPA mutations alone and with co-existing molecular defects of two other genes: NPM1, FLT3 are discussed in cases of AML with normal karyotype